2018
DOI: 10.1371/journal.pone.0203761
|View full text |Cite
|
Sign up to set email alerts
|

Activity changes in neuron-astrocyte networks in culture under the effect of norepinephrine

Abstract: The concerted activity of neuron-glia networks is responsible for the fascinating dynamics of brain functions. Although these networks have been extensively investigated using a variety of experimental (in vivo and in vitro) and theoretical models, the manner by which neuron-glia networks interact is not fully understood. In particular, how neuromodulators influence network-level signaling between neurons and astrocytes was poorly addressed. In this work, we investigated global effects of the neuromodulator no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 88 publications
3
24
0
Order By: Relevance
“…Here we report that NE suppresses ammonium‐induced [Ca 2+ ] i oscillations in neurons and evokes Ca 2+ response in astrocytes. The same findings were reported in the work (Bar El, Kanner, Barzilai, & Hanein, ). The authors showed that NE induced Ca 2+ response in astrocytes and suppressed the activity of neurons in cortical mixed neuroglial cell cultures.…”
Section: Discussionsupporting
confidence: 91%
“…Here we report that NE suppresses ammonium‐induced [Ca 2+ ] i oscillations in neurons and evokes Ca 2+ response in astrocytes. The same findings were reported in the work (Bar El, Kanner, Barzilai, & Hanein, ). The authors showed that NE induced Ca 2+ response in astrocytes and suppressed the activity of neurons in cortical mixed neuroglial cell cultures.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that astrocyte maturation was time dependent and marker dependent, as shown by the profile of maturation of “immature” hiPSC‐A (i.e., hiPSC‐A cultured for 60DIV prior to use) in coculture, which was less marked than 90DIV hiPSC‐A, with, however, the exception of two markers, Cx43 and AQP4. These early changes in AQP4 and Cx43 profiles suggest a neuronal influence on their expression not related to astrocyte maturation, and parallels previous literature on rodent astrocytes showing elevations in calcium intercellular signaling and changes in astrocyte volume in response to neuronal activity.…”
Section: Discussionsupporting
confidence: 87%
“…In this respect, and beyond our preliminary observations based on RNA levels, previous literature on rodent astrocytes had already shown that Cx43 and AQP4 function is modulated by neuron-astrocyte interactions, as suggested by elevations in calcium intercellular signaling 46,47 and changes in astrocyte volume 48,49 , respectively, in response to neuronal activity.…”
Section: Discussionsupporting
confidence: 50%